Reviews of environmental contamination and toxicology. volume 214 - Whitacre, David M.; SpringerLink (Online service). (New York Springer, 2011)
CONTENTS Foreword Preface Evaluating Risks of Acquired Clinical Vulnerability Among Subjects Exposed to E-waste Anup Kumar Srivastava, Chandrasekharan Nair Kesavachandran and Sushil Kumar Aerospace Toxicology Overview: Aerial Application and Cabin Air Quality Arvind K. Chaturvedi Land Application of Sewage Sludge: Physico-chemical and Microbial Response Rajeev Pratap Singha, Pooja Singhc, M. Hakimi Ibrahimb and Rokiah Hashim The Accumulation of Heavy Metals in Selected Medicinal Plants Hemen Sarma, Suresh Deka, Hemen Deka and Rashmi Rekha Saikia Effects of Organic Herbicides on Phototrophic Microbial Communities in Freshwater Ecosystems Stéphane Pesce, Agnès Bouchez and Bernard Montuelle Essential Roles and Hazardous Effects of Nickel in Plants Muhammad Sajid Aqeel Ahmad and Muhammad Ashraf Index
Foreword -- Preface -- Evaluating Risks of Acquired Clinical Vulnerability Among Subjects Exposed to E-waste -- Aerospace Toxicology Overview: Aerial Application and Cabin Air Quality -- Land Application of Sewage Sludge: Physico-chemical and Microbial Response -- The Accumulation of Heavy Metals in Selected Medicinal Plants -- Effects of Organic Herbicides on Phototrophic Microbial Communities in Freshwater Ecosystems -- Essential Roles and Hazardous Effects of Nickel in Plants -- Index.
Electronic reproduction.
Keywords: Environmental toxicology; Environmental management; Pollution; Electronic books